Subgingival Periodontal Pre-Treatment Irrigation with 0.75% Boric Acid as an Adjunct to Mechanical Periodontal Therapy in Localised Chronic Periodontitis - Banerjee, Swagata; Mathur, Aditi; Shetty, Neema; Makhijani, Barkha; Bali, Ashish; Manohar, Balaji (Journal of Nepalese Society of Periodontology and Oral Implantology, 2019)
Introduction: Dental plaque is the primary aetiological factor for periodontal disease. Scaling and root planing may fail to eliminate periodontal pathogenic species because of limited access to the root surface and tissue-invading properties of some periodontal pathogens. Considerable attention has been devoted to the possibility of using antimicrobial agents such as chlorhexidine to eliminate periodontal pathogens with limited success. Studies show that boric acid has antibacterial and anti-inflammatory properties. Objective: The aim of the study was to evaluate the efficacy of 0.75% boric acid when used as a subgingival irrigation agent as an adjunct to oral prophylaxis in treatment of localised chronic periodontitis. Methods: A total of 40 individuals who reported to the dental college with localised periodontitis (pocket depth of ≥ 6 mm) participated in the study. Plaque Index, Gingival Index and Probing Pocket Depth were recorded at baseline and one month post irrigation with either 0.75% boric acid (Group I) or 0.2% chlorhexidine (group II). Intragroup comparison was done using student “t” test. Results: Intra-group comparison in Group I and Group II showed significant results for reduction in Plaque Index, Gingival Index and Probing Pocket Depth. Significant results observed for reduction of Probing Pocket Depth (<0.025) between the two groups - Plaque Index (>0.54) and Gingival Index (>0.93) were non-significant one month postoperatively. Conclusion: The results of this study suggest that 0.75% boric acid has similar efficacy as 0.2% chlorhexidine as a coadjuvant in the treatment of periodontitis.